Implementation of Fuzzy Logic in Yeast Concentration and Fermentation Time for Tempeh Quality - Almaida Pramesti; Aura Fadhilah; Belvana Fazwa Athallah; Grace Octo Suma Panjaitan; Nastiti Ayu Utami; Prima Ananta Nugraha; Rohidi; Mrr Lukie Trianawati; Daffa Zulqisthi; Muhammad Faiz Assariy; Chika Hayya Asabillah (Batrisya Education, 2025)
This study investigates the application of fuzzy logic to optimize yeast concentration and fermentation time in tempeh production. Tempeh, a traditional Indonesian food made by fermenting soybeans, requires precise conditions to ensure high quality, including optimal yeast concentration and incubation duration. Fuzzy logic provides a flexible approach by allowing variable inputs within ranges, rather than fixed values, making it ideal for controlling uncertain factors in fermentation. The study used MATLAB software for fuzzy logic modeling, incorporating yeast concentration and fermentation time as input variables and tempeh quality as the output. Key parameters for each input were defined, and fuzzy rules were applied to predict tempeh quality under varying conditions. Results indicate that a yeast concentration of 30% and a fermentation time of 53 hours yield a quality rating of 6.9, indicating satisfactory tempeh. The fuzzy model proved accurate, with close alignment between predicted and actual results, underscoring fuzzy logic's effectiveness in refining fermentation processes.